PROSEDUR PEMBERIAN KREDIT MODAL USAHA PADA BUMDESA HARAPAN JAYA LESTARI DESA SIMPANG HARAPAN - Nurmala Sari (Jurnal Ilmiah Cano Ekonomos, 2023)
This journal was written with the aim of knowing and understanding the procedures for granting business capital loans to Bumdesa and settlement of bad loans to Bumdes in order to support the creation of sound credit practices. This research was conducted at Bumdesa Harapan Jaya Lestari, Simpang Harapan Village, North Tambusai District. BUMdesa Harapan Jaya Lestari is engaged inSavings and Loan Units, livestock units, trading units, and agricultural units. The data analysis technique used is descriptive method. With data collection techniques are interviews and documentation. The results of the study show that the provision of credit as business capital to BUMDesa Harapan Jaya Lestari has implemented the 5 C principles (character, capacity, collateral, capital andcondition). The process of resolving bad loans in the credit agreement at BUMDes Harapan Jaya Lestari is through a repressive effort, namely an effort in the form of resolving bad credit problems to the debtor using the principle of negotiation based on kinship.